Comparación de dos hormonas naturales y una química para el enraizamiento de estacas de Jícama (smallanthus sonchifolius)(poepp.) h.rob en la provincia de Cotopaxi, barrio Salache Bajo (CEASA) en el periodo 2018-2019. - Yasig Quinga, Carlos Alfredo (2021)
This research work was carried out at the Centro Experimental Salache (CEASA) of the Technical University of Cotopaxi (UTC), located at coordinates X: 0764249; Y: 9889461, at 2734 meters above sea level, with the main objective of determining the rooting potential of two natural hormones and a chemical in Jicama cuttings (Smallanthussonchifolius) in the Province of Cotopaxi, Barrio SalacheBajo in the period 2018 - 2019. The proposed objectives In this study they were: quantify the rooting of jicama cuttings through non-destructive invasive measurements and with the application of two natural hormones and a chemical hormone; determine the plant mortality index of the different treatments in the jicama cuttings; conduct a cost-benefit analysis to determine the most profitable method for rooting jicama cuttings; To carry out the objectives, an AxB experimental design was proposed, with nine (9) treatments and three doses, giving a total of twenty-seven (27) experimental units. The results of the research revealed that when applying the rooting agent at 15%, the percentage of rooting in the jicama cuttings increased, at the beginning of the study a low presence of rooting was observed and at the end a considerable increase in these values was obtained, the percentage of the mortality rates revealed that this parameter was low, representing 19% throughout the entire time of the project, and an attachment of 89%, as well as the appearance of a root mass with 13.33 cm in length at the end of the study, the best The treatment given in terms of root mass growth was dosing at 15% after 40 days of data collection.